Peran Perpustakaan Keluarga dalam Meningkatkan Minat dan Keterampilan Membaca Anak - Huriyah, Lilik (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
The interest and reading skills of Indonesian society is still very low compared to other developing countries in the world. One of the factors causing low levels of interest and reading skills of children in Indonesia is the family environment that is not supportive yet. Therefore, it needs the support of the family in the form of family library facilities. By the existence of the family library, it will help to improve the children's interest and skills in reading. The family library has a veryimportant role as a means to increase the children's interest and reading skills. Some of these roles include as a motivator, educator, facilitator, instructor and recreational space.